A cross-cultural examination of Australian, Chinese and Vietnamese consumers' attitudes towards a new Australian wine product containing Ganoderma lucidum extract. (January 2019) - Nguyen, Anh N.H.; Johnson, Trent E.; Jeffery, David W.; Danner, Lukas; Bastian, Susan E.P.
Abstract: Ganoderma lucidum ( GL ) is a woody mushroom that has been widely used for many centuries in traditional Chinese medicine. Its bioactive-compounds are believed to promote longevity and prevent diseases in humans. With the close proximity of emerging Asian markets, Australian winemakers are beginning to adopt consumer-centric wine product development as a strategy to generate wines with profiles that meet the specific demands of these consumers. This cross-cultural study recruited 412 wine consumers (Chinese, Vietnamese and Australian) to participate in a survey to understand wine consumers' potential acceptance and self-reported intent towards new wine products produced with GL extracts and the relationship of their responses with wine neophobicity across cultures. Findings revealed that all consumer groups accepted the notion that GL wine products would be worth tasting and they would try them at social events, with Vietnamese consumers being particularly interested. Using the wine neophobia scale (WNS), three segments containing wine neophiles ( n  = 110), neutrals ( n  = 190) and wine neophobes ( n  = 112) were identified. The results revealed that Australian and Chinese participants were significantly more wine neophilic, compared to Vietnamese. As expected, neophiles were more prepared to taste and purchase GL wine products compared to neophobes across all three countries, although no gender differences were observed. The study provides the wine industry insights about consumers' attitudes towards a new GL wine product targeted to Australian and Asian markets that could help develop new niche wine categories and enhance consumers' satisfaction. Highlights: Australian, Chinese and Vietnamese consumers' attitudes towards Ganoderma wine products was explored. Most participants across the three nations were open to trying such new wine products. Vietnamese consumers were most open to the concept of wines containing Ganoderma . Wine neophobia status significantly influenced consumers' attitudes towards Ganoderma wine products. Findings of consumers' attitudes towards new wine products are insightful for the wine industry.